Propositions pour un dictionnaire des moyens d’intensification - Pilecka, Ewa (Studia Romanica Posnaniensia, 2015)
The growing body of literature on intensifiers enables us to circumscribe the scope of the phenomenon more accurately and to identify rigorously its linguistic realizations. Yet, the latter are clearly underrepresented or inconsistently treated both in general dictionaries and in textbooks. That is why the need arises to work up a dictionary devoted to means of intensification so that it can serve as a tool to students of French. Rather than simply listing these means, it should be conceived of as a lexicongrammar enabling users both to vary particular forms and to respect syntactic and combinatory constraints. Additionally, it should account for when registers can be conveniently switched. The present paper aims at giving some hints on how such a disctionary should be prepared.